Analisis Efektivitas Pajak Restoran Terhadap Peningkatan Pendapatan Asli Daerah Kabupaten Klaten: Studi Kasus BPKPAD Kab. Klaten - Margaheni, Lisa Dyah; Kusuma, Indra Lila; Samanto, Hadi (Jurnal Ilmiah Keuangan Akuntansi Bisnis, 2025)
The purpose of this research is to determine the level of effectiveness and contribution of restaurant taxes to increasing local original income, and the obstacles and efforts made by the Regional Asset Handling Financial Management Agency in increasing local original income. The method used by researchers is a qualitative descriptive method. The data collection techniques used were interviews, observation and documentation. The results of this research show that the effectiveness of the restaurant tax in 2018-2019 was very effective with an average of 118.14%, while the contribution level of restaurant tax to Original Regional Income in 2018-2022 obtained a value of 1.92%, which is categorized as very poor. The obstacle factors obtained from the Regional Asset Handling Financial Management Agency are the lack of data collection and supervision from the regional government, the lack of awareness of taxpayers in carrying out restaurant taxes, and the phenomenon of natural disasters. Efforts made are by providing incentives to collection officers, collecting data on taxpayers, supervising tax administration and providing outreach regarding restaurant tax collection.